The Effect of Prevention Education of Dengue Hemorrhagic Fever on Knowledge and Attitudes of Family Heads - Nur Isriani Najamuddin; Wahyu Hidayat; Masyita Wahab; Mutmainna; Reffi Nantia Khaerunnisa (Genius Journal, 2020)
Introduction : Assistance and health education about DHF is one way that is used to increase one's knowledge about DHF with the aim of changing or influencing human behavior in the prevention of dengue. The purpose of assistance and education about DHF is to inform the public about the disease. Objective : To determine the effect of assistance and educationto prevent dengue hemorrhagic fever against the knowledge and attitudes of family heads in Batetangnga village. Method : used pre-experimental research with the form of one group pretest and posttest design. The number of samples in this study were 20 people. Sampling in this study using non-probability sampling technique with Consecutive sampling method. Results : of the study were obtained by using the Mc Nemar test and Wilcoxon signed ranks test. Conclusion : showed that there was an effect of assistance and education (penyu) prevention of dengue haemorrhagic fever (DHF) on knowledge (p=0.001) and attitudes of family heads (p = 0.001) in Batetangnga Village.